(untitled) (Ascendens Asia Singapore – Union Christian College Philippines Journal of Multidisciplinary Research Abstracts, 2021)
Kindergarten education provides a strong foundation for learners to achieve better later in life. With the ongoing health crisis due to the COVID 2019 pandemic, the Department of Education adopted the Basic Education Learning Continuity Plan (BE-LCP) for the SY 2020-2021, which demands a holistic approach and stronger partnership among schools, households, and communities and necessitates the complementary and broader roles of parents, guardians, and other households’ partners and members of the community to support the learning process of the students at home. This study determined the instructional competence of the kindergarten para teachers of Candon City Division as a basis for developing para-teacher empowerment initiatives. Specifically, it looked into the level of instructional competence of para-teachers in teaching kindergarten along with a.) Teaching Language Literacy Skills b,) Mathematical and Scientific Thinking c.) Learning Through Play d.) Application of Kindergarten Principles and the significant difference in the para-teachers instructional competence when grouped according to their profile. It utilized the descriptive developmental method of research with the researcher-made questionnaire to gather data from 202 respondents. The data gathered were treated statistically using frequencies, means, and percentages. It was found out that the para teachers are highly competent in all areas. Still, there are indicators per area that needed enhancement to make them more ready and equipped in facilitating their children’s learning. Hence, the Para Teachers EmpowermentInitiatives are recommended. The primary data gathering tool of the study was a researcher-constructed questionnaire, which was validated by education supervisors, school heads, and master teachers who are experts in research and kindergarten education. The data gathered was treated with descriptive and inferential statistics. It was found out that the para teachers are highly competent in all areas, but there are indicators per area that need enhancement to make them more ready and equipped to facilitate their children’s learning. Furthermore, the highest educational attainment of the respondents was found to be a significant factor in the para teachers’ teaching competence. Hence, the Para Teachers Empowerment Initiatives are recommended for adoption.